Fasdhu therapy to reduce excess levels of substances in the human body - Darmadi, Darmadi; Juariah, Siti; Sukri, Sukri (Universitas Muhammadiyah Magelang, 2021)
Tarai Bangun Hamlet IV, Tarab Mulya Village is a village located in Kampar Regency where the majority of the people come from the Minang and Javanese tribes. They like to eat fatty foods that trigger an increase in body fat levels. This service is carried out with the aim of helping people who experience high blood sugar, cholesterol and uric acid levels with the phlebotomy technique (fasdhu). The method used is to provide health education, followed by checking blood sugar, cholesterol and uric acid. High levels are then performed Fasdhu. Based on the examination of blood sugar, cholesterol and uric acid checks on 37 respondents, it was found that 10 respondents had high levels. Fasdhu treatment was carried out on respondents who had blood sugar levels of 163 mg/dl, cholesterol 240.75 mg/dl and uric acid 8.95 mg/dl. After fasdhu treatment, the levels decreased to 107 mg/dl, 200 mg/dl and 7.15 mg/dl, respectively. Based on this treatment, it was concluded that the phlebotomy technique (fasdhu) could be recommended as an effort to reduce blood sugar, cholesterol and uric acid levels.